2011
DOI: 10.1002/cncr.26369
|View full text |Cite
|
Sign up to set email alerts
|

Small renal masses progressing to metastases under active surveillance

Abstract: Purpose We conducted a systematic review and pooled analysis of small renal masses under active surveillance to identify progression risk and characteristics associated with metastases. Materials and Methods A MEDLINE search was performed to identify all clinical series reporting surveillance of localized renal masses. For studies reporting individual level data, clinical and radiographic characteristics of tumors without progression were compared to those progressing to metastases. Results 18 series (880 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
239
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(260 citation statements)
references
References 67 publications
15
239
1
5
Order By: Relevance
“…26 Indeed, a previous review showed that most small renal masses remain radiographically static after an initial period of surveillance. 28 The improved selection of surgical candidates may depend on the identification of biomarkers that can help distinguish benign and malignant disease, as well to accurately predict tumours that will metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…26 Indeed, a previous review showed that most small renal masses remain radiographically static after an initial period of surveillance. 28 The improved selection of surgical candidates may depend on the identification of biomarkers that can help distinguish benign and malignant disease, as well to accurately predict tumours that will metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…With emerging evidence regarding its safety, the role of AS for small RCCs has also increased. [27][28][29][30][31][32][33] In this study, AS was recommended by 21% of urologists for C3, 30% for C4, 48% for C5, and 67% for C6. …”
Section: Discussionmentioning
confidence: 83%
“…Following the diagnosis and conclusion of the observation, larger tumors and larger tumor volumes tended to progress. Significant differences in both the average growth rate (0.80 cm/year vs. 0.3 cm/year) and the average volumetric growth rate (27.1 cm 3 /year vs. 6.2 cm 3 /year) have also been observed [25].…”
Section: Discussionmentioning
confidence: 92%